Exemplars of kingship art, tradition, and the legacy of the Akkadians - Eppihimer, Melissa 1979- (Oxford Oxford University Press USA - OSO, 2019)
Exemplars of Kingship conveys the astonishing life of the art of the Akkadian kings by assessing ancient and modern responses to its dynamic forms and transformative ideologies of kingship.
Cover -- Exemplars of Kingship -- Copyright -- CONTENTS -- List of Figures and Tables -- Acknowledgments -- Notes on Names, Dates, and Languages -- List of Abbreviations -- 1. Behold Sargon -- 2. Exemplars of Kingship and the Art of Memory -- Remembering the Akkadians -- Visual Traditions and Interpictoriality -- The Temporalities of Images -- Memories and Traditions beyond Our Control -- 3. Triumphant Kings and the Legacy of Akkadian Steles -- The Privileged Status of the Stele of Naram-​Sin -- Life and Death in Akkadian Victory Monuments -- Distinguishing Responses: The Zagros Rock Reliefs -- Ideal Kingship and the Steles of Shamshi-​Adad I and Dadusha -- Late Entries: The Victory Monuments of Darius I -- The Legacy of the Stele of Naram-​Sin -- 4. Royal Bodies and the Legacy of Akkadian Statues -- The Statues of the Akkadian Kings -- The Absent Legacy: The Historiography of Akkadian Royal Statues -- Emulation and Critique in the Statues of Gudea -- The Statues of the Kings of Ur -- Akkadian Tassels at Mari and Eshnunna -- Akkadian or Akkadian Imitations: The Statues of Puzur-​Inshushinak -- Akkadian or Akkadian Imitations: The Statues from Ashur -- The Visual Legacy of Akkadian Royal Statues -- 5. Curly-​Haired Heroes and the Legacy of Akkadian Seals -- Seals and Kingship in the Akkadian Period -- Modern Interpretations of Akkadian Cylinder Seals -- The Lahmu and the Contest Scene after the Akkadians -- The Akkadian Qualities of Middle Assyrian Art -- The Lion-​Wielding Heroes of Khorsabad -- The Assyrian Forms and Functions of the Khorsabad Heroes -- Remembering the Akkadians in the Neo-​Assyrian Period -- The Visual Legacy of Akkadian Seals -- 6. Allusions and Illusions -- Allusions to and Illusions of the Akkadians -- Memories of the Akkadians beyond Mesopotamia -- Other Memories, Other Exemplars -- Notes -- References -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Portrait sculpture, Ancient-Themes, motives; Art, Akkadian-Influence; Kings and rulers in art; Iraq-Kings and rulers; Electronic books; Hochschulschrift